2016
DOI: 10.1080/23746149.2016.1181986
|View full text |Cite
|
Sign up to set email alerts
|

Continuum modelling of semiconductor heteroepitaxy: an applied perspective

Abstract: Semiconductor heteroepitaxy involves a wealth of qualitatively different, competing phenomena. Examples include threedimensional island formation, injection of dislocations, mixing between film and substrate atoms. Their relative importance depends on the specific growth conditions, giving rise to a very complex scenario. The need for an optimal control over heteroepitaxial films and/or nanostructures is widespread: semiconductor epitaxy by molecular beam epitaxy or chemical vapour deposition is nowadays explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 255 publications
(371 reference statements)
0
36
0
Order By: Relevance
“…The evolution displayed in Figure 6 was subsequently simulated [33] by also taking into account surface-energy anisotropy [23], yielding results even closer to the experimental ones. It has been further demonstrated that merging can also be obtained directly during growth (by raising the growth temperature) [21,31]. The suspended film is found [18] to still profit of the ability of the underlying pillars to release thermal strain by tilting.…”
Section: Suspended Filmsmentioning
confidence: 93%
See 1 more Smart Citation
“…The evolution displayed in Figure 6 was subsequently simulated [33] by also taking into account surface-energy anisotropy [23], yielding results even closer to the experimental ones. It has been further demonstrated that merging can also be obtained directly during growth (by raising the growth temperature) [21,31]. The suspended film is found [18] to still profit of the ability of the underlying pillars to release thermal strain by tilting.…”
Section: Suspended Filmsmentioning
confidence: 93%
“…The suspended film displayed in Figure 6 was obtained [30] by prolongated high-temperature annealing of vertical Ge crystals on Si pillars. Temporal snapshots of the evolution are also displayed, together with a corresponding continuum simulation [31] (panel b). The latter was performed exploiting a diffusion-equation approach, implemented in a phase-field framework [22], where the only contribution to the chemical potential µ (determining material flow) was the Mullins [32] term µ = −kγ, where k is the local curvature and γ the surface-energy density.…”
Section: Suspended Filmsmentioning
confidence: 99%
“…A semi-implicit time discretization scheme is used in order to solve the set of equations defined in (4) and (5), and it is reported in detail in Appendix B 1. It consists of solving four second-order partial differential equations (PDEs) for each amplitude function.…”
Section: B Numerical Approachmentioning
confidence: 99%
“…In the past few decades, phase-field (PF) models have been used extensively for modeling the ordering of nanoand micro-structures. Such models provide a suitable framework for the investigation of a wide range of phenomena such as solidification processes, grain growth, surface diffusion, heteroepitaxy, and even dislocation dynamics [1][2][3][4][5]. Despite their versatility, strong limitations arise for PF models when looking at material properties closely related to atomic arrangement and periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…The central issue is that the dynamics of the surface morphology is coupled to the elastic strain in the system, so dynamic models require solving the elasticity problems throughout the film and substrate at each time step and are limited by storage limitations for 3-dimensional problem. Simulations involving the full elasticity problem are limited to one or few islands [23] [24]. Only one recent work [25] explored a large number of islands using a large-scale 3-dimensional calculation.…”
Section: Introductionmentioning
confidence: 99%